2019
DOI: 10.1080/07399332.2018.1535600
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and worries of pregnant women living through disaster recovery

Abstract: The health and well-being of pregnant women during and after natural disasters remains an international concern. In this mixed methods study we described pregnant women's mental health, psychosocial concerns and sources of stress living in New Orleans during long term recovery from Hurricane Katrina. Our survey of 402 pregnant women indicated poor social support was associated with higher levels of depression symptomology, post-traumatic stress disorder, anxiety, and stress. Women were interviewed and describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…32 Qualitative studies regarding natural disasters or health crises also corroborate these findings: pregnant women have expressed distress about body image, family planning, and prevention concerns, particularly regarding risks for birth defects regarding the Zika outbreak; 33 and concerns across a variety of domains in the aftermath of Hurricane Katrina, such as the health of the child and family, housing and finances, breastfeeding, mental health, and loss. 34 In the qualitative findings in our study, many women commented about the need to remain calm and engage in self-care, not only for their own wellness but also for the wellness of their child and family. It is important to note that a lifetime history of depression can be one of the most important predictors of future depressive episodes in the perinatal period 35 ; our study is limited in that we were unable to obtain a medical history from participants.…”
Section: Discussionmentioning
confidence: 66%
“…32 Qualitative studies regarding natural disasters or health crises also corroborate these findings: pregnant women have expressed distress about body image, family planning, and prevention concerns, particularly regarding risks for birth defects regarding the Zika outbreak; 33 and concerns across a variety of domains in the aftermath of Hurricane Katrina, such as the health of the child and family, housing and finances, breastfeeding, mental health, and loss. 34 In the qualitative findings in our study, many women commented about the need to remain calm and engage in self-care, not only for their own wellness but also for the wellness of their child and family. It is important to note that a lifetime history of depression can be one of the most important predictors of future depressive episodes in the perinatal period 35 ; our study is limited in that we were unable to obtain a medical history from participants.…”
Section: Discussionmentioning
confidence: 66%
“…38 Sources of resilience were identified in these data and are supported by past research that has explored resilience among perinatal women during disasters. Virtual media platforms (texting, video calls), 39,40 and engaging in selfcare behaviors such as getting recommended sleep and exercise 41 were identified as protective coping behaviors in the quantitative data. Qualitative data suggested that social support, and specifically partner and emotional support, 42 gratitude and optimism, 43,44 and the management or shifting of expectations 45 were significant protective factors for pregnant and postpartum women, particularly during exposure to significant environmental stressors.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature highlights how natural disasters impact psychologically on pregnant women, which can develop short and long term traumas, often resulting in increased levels of stress and anxiety (27,28). During the emergency, one of the main concerns of pregnant women, as con rmed by our study, is the safety and the well-being of their unborn baby (22,(29)(30)(31). Other main concerns are the challenges related to the loss of one's home, the displacement, and the move to other temporary housing solutions.…”
Section: Discussionmentioning
confidence: 51%
“…In its primary intention, the research was designed to inform local action on mothers and infants' care. Given the limited availability of studies exploring the emergency responses from the mothers' perspective (22), and the ongoing obstacles and challenges affecting IYCF-E worldwide (e.g. untargeted donations of BMS, uncoordinated infant feeding interventions, lack of programs and policies) (23)(24)(25), ten years later the authors decided to re-analyze the collected data with a focus on the recommended practices for breastfeeding protection, promotion and support.…”
Section: Introductionmentioning
confidence: 99%